Pengaruh Frekuensi Penggorengan Bahan Makanan Terhadap Angka Peroksida - Yunita - Nazarena; Eliza Eliza; Terati Terati; Ayu Meilina (Jurnal Sehat Mandiri, 2022)
Evaporation of water in food during frying causes fat break down into hydroperoxides. The peroxide indicates the initial stage of oxidation. This study aims to determine the exact temperature and time of frying and the effect of frying frequency on the peroxide. The research was carried out in 2 stages, namely preliminary research aimed at getting the right temperature and cooking time, the main research aimed at getting the peroxide value of cooking oil. This study used experimental research, a completely randomized design with five treatments, two replications and deep frying. Research object: "X" brand cooking oil. Determination of peroxide using the titration method. The effect of frying frequency on peroxide was analyzed by ANOVA (α = 5%). The treatment that had a significant effect was continued with LSD. The results showed that frying tempeh (7-9 minutes, temperature 120-130°C), tofu (6-9 minutes, temperature 120-130°C), fish (9-10 minutes, temperature 140-170°C). The peroxide for frying tempeh is the 1st frequency (0.375±0.0021), 20th (0.950±0.198), frying tofu is the 1st frequency (0.385±0.777), 20th (0.710 ±0.042), frying fish is 1st the frequency (0.325±0.163) and 20th (1,470 ±0.007). Conclusion, the frequency of frying has a significant effect on the peroxide with p-values ​​of tempe (0.016), tofu (0.088), fish (0.093). It is hoped the next research can measure the acid number and smoke deposit at each frequency of frying.